2003
DOI: 10.1016/j.physletb.2003.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Color ferromagnetism in quark matter

Abstract: We show a possibility that there exists a color ferromagnetic state in quark matter, in which a color magnetic field is spontaneously generated. The state arises between the hadronic state and the color superconducting state when the density of quarks is varied. Although the state ( Savvidy state ) has been known to involve unstable modes of gluons, we show that the modes compose a quantum Hall state to stabilize the ferromagnetic state. We also show that the order of the phase transition between the state and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(49 citation statements)
references
References 19 publications
2
47
0
Order By: Relevance
“…We have shown [7] that the quarks play an important role for the stabilization of the color magnetic field. Namely, unstable modes of gluons, which are present [13] under the color magnetic field, have been shown to be stabilized with their condensation, just as scalar fields in Higgs potentials.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…We have shown [7] that the quarks play an important role for the stabilization of the color magnetic field. Namely, unstable modes of gluons, which are present [13] under the color magnetic field, have been shown to be stabilized with their condensation, just as scalar fields in Higgs potentials.…”
mentioning
confidence: 97%
“…Namely, unstable modes of gluons, which are present [13] under the color magnetic field, have been shown to be stabilized with their condensation, just as scalar fields in Higgs potentials. The condensation leads to a fractional quantum Hall state of the gluons [14,7] with a color charge density. This color charge density of the gluons is supplied by quarks.…”
mentioning
confidence: 99%
“…In [20,21], a new approach was proposed to achieve the stable vacuum state. There, the solution with It should be emphasized that the solution found in [20] is stable only with respect to (2+1)-dimensional perturbations. However, the true vacuum state should be stable with respect to (3+1)-dimensional perturbations as well, i.e., against non-uniform perturbations along the x 3 axis parallel to the chromomagnetic field direction.…”
Section: The Effective Dimensional Reduction In the Gluon Sectormentioning
confidence: 99%
“…In particular, The principal difficulty in finding a stable color ferrromagnetic state is that a local minimum of the action can not be obtained, since the corresponding field configuration proved to be spatially inhomogeneous. In order to circumvent this difficulty, the method earlier applied in analyzing the quantum Hall effect [19] was used in [20,21]. It was demonstrated that a spatially homogeneous state of the gluon field can be obtained by effectively reducing the dimensions of the problem from D = (3 + 1) to D = (2 + 1) and employing for gluons the technique used in [19,22] for the description of the quantum Hall effect in a (2 + 1)-dimensional Fermi system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation